Building Wireless Community Networks, Second Edition - Flickenger, Rob (O'Reilly, 2011)
Building Wireless Community Networks is about getting people online using wireless network technology. The 802.11b standard (also known as WiFi) makes it possible to network towns, schools, neighborhoods, small business, and almost any kind of organization. All that's required is a willingness to cooperate and share resources. The first edition of this book helped thousands of people engage in community networking activities. This revised and expanded edition adds coverage on new network monitoring tools and techniques, regulations affecting wireless deployment, and IP network administration, including DNS and IP Tunneling.